Splitting the firm between the entrepreneur and the venture capitalist with the help of stock options - Chua, Jess H.; Woodward, Richard S. (Journal of Business Venturing, 1993)
The Net Present Value (NPV) Rule provides the basic principle underlying the sharing of ownership in a new venture. The principle often fails because the entrepreneur and the venture capitalist cannot agree on the potential profitability value of the venture. First, the venture capitalist may simply have a less optimistic interpretation of the data related to the venture's profit potential. We refer to this discrepancy between the expectation of the entrepreneur and that of the venture capitalist as the expectation gap. Second, the venture capitalist knows that for the venture's potential to be realized, the entrepreneur/manager must devote his full effort to the success of the organization. This is not a problem if the entrepreneur owns the entire project. Once the ownership is shared, however, especially when the venture capitalists own the majority of the shares, the entrepreneur has a financial incentive to apply less than the diligence required to control costs and protect the interests of the outside equity holders. This financial incentive arises because any perk, including leisure or shirking, consumed by the entrepreneur does not have to be shared with the venture capitalist, while every dollar saved does. This is not solved by the venture capitalist acquiring a larger percentage of the company. That will only exacerbate the problem as it decreases the cost to the entrepreneur of each dollar of the company's funds spent for the perk. We refer to this as the motivation problem. In the article, we show how stock options can be used to deal effectively with both problems. First, stock options are always worth more to the optimist than to the pessimist. Thus, there will be a reverse valuation gap with respect to the stock options. We show that by issuing stock options to the entrepreneur, it is possible to close the expectation gap. To solve the motivation problem, the entrepreneur's stake must be increased to the extent where the cost to him of excessive consumption of perks will be as high as the benefit he derives. This can be accomplished by taking advantage of two valuation characteristics of stock options. First, stock options are worth only a fraction of the value of the underlying equity shares. Thus, it is easier for the venture capitalist to give up these, rather than the underlying equity shares. Second, the stock options will fluctuate with the venturing firm's value at a higher rate than the entrepreneur's percentage ownership. Thus, by issuing the entrepreneur a combination of equity shares and stock options, it is possible to increase significantly the entrepreneur's cost of “shirking” or “excessive consumption of perks.” Under idealized conditions, it is possible to design a financing arrangement that eliminates the motivation problem. The principles discussed here provide benchmarks that both the entrepreneur and the venture capitalist may wish to bring to the negotiating table. In the end, there is no substitute for the building of trust between the two to give the venture the maximum chance of success.